Obtaining of small-dispersed microspheres using the method of mechanical and plasma separations - Бaтрышев, Д.Г.; Рамазанов, Т.С.; Досболаев, М.К.; Габдуллин, М.Т.; Ерланулы, Е. (Recent Contributions to Physics, 2016)
In this paper the method of obtaining of small-dispersed microspheres based on a mechanical and plasma separations is considered. This method allows for obtaining microparticles with high dispersion produced from any materials. The advantages of this technology compared to other analogues are its simplicity and low energy consumption. In addition, this method can be used as a tool which can control the lower and upper limit in particle size distribution in powder. This procedure could be a promising application for obtaining of emboli in cancer treatment.